The Digestion, Absorption and Utilization of Refined Palm Oil, Palm Olein and Palm Stearin in the Rat - Ng, Tony Kock Wai; Khor, Hun Teik; Chong, Yoon Hin (1988)
A nutritional evaluation of refined, bleached and deodorised (RBD) palm oil and its fractionation products, RBD palm olein and RBD palm stearin in terms of their digestibility, rate of absorption and food efficiency in rats, shows that RBD palm olein is a better oil by these criteria than RBD palm stearin and the unfractionated RBD palm oil. Nevertheless, the nutritional indices reported for RBD palm oil and RBD palm stearin are well within the range reported for most cooking oils and fats. The digestibility and food efficiency of RBD palm olein are comparable to that of soybean oil, being 97% and 98% respectively of the values found for the latter oil, although the absorption rate of RED palm olein is 10% less than that obtained for soybean oil.